Environment-friendly easy-to-process ceramic rock plate with low crystalline silicon dioxide content and production method thereof
By reducing the crystalline silica content in ceramic rock slabs and converting them into amorphous silica, the problems of silicosis risk and cold-working damage in ceramic rock slab production are solved, and the processability and fracture toughness of ceramic rock slabs are improved.
Patent Information
- Application Number
- CN202411321879.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-23
AI Technical Summary
High content of crystalline silica in the production process of ceramic rock slabs leads to high risk of silicosis and high cold-work damage rate.
Through innovative design and firing system of ceramic rock slab formula system with low crystalline silica content, efficient regulation is carried out to reduce the content of crystal silica in the ceramic rock slab body layer and convert it into amorphous silica and Other crystal phases reduce dust generation and stress and improve processability.
It effectively reduces the risk of silicosis during the production and processing of ceramic rock slabs, reduces the cracking loss of cold processing, and improves the fracture toughness and processability of ceramic rock slabs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of building ceramics, and in particular to an environmentally friendly, easy-to-process ceramic rock slab with low crystalline silicon dioxide content and a production method thereof. Background Art
[0002] Compared with traditional porcelain tiles, ceramic rock slabs, as a new type of ceramic decorative product in recent years, have the characteristics of large specifications, fewer seams, better density, stronger mechanical properties, richer and more realistic surface textures, etc. Therefore, ceramic rock slabs have a wider range of applications than traditional porcelain tiles. They can not only be used as wall and floor tiles, but also as a multifunctional decorative material. Through secondary processing such as cutting and drilling, they can be made into different shapes and specifications and used in different areas of the home such as dining tables, coffee tables, wardrobes, cabinet doors, background walls, etc.
[0003] However, the current ceramic rock slab blanks use quartz, clay, and feldspar as the main raw materials. The weight percentage of crystalline silicon dioxide in the physical composition of these raw materials is generally 20%-40%, while the weight percentage of crystalline silicon dioxide in the physical composition of the produced ceramic rock slab products is generally higher than 10%. Whether in the early stage of ceramic rock slab blank raw material processing or the later stage of ceramic rock slab product cutting, grinding and other processing, a large amount of high crystalline silicon dioxide content respirable dust will be generated. This dust can be deposited in the lungs, causing characteristic inflammatory reactions, extensive nodular fibrosis of lung tissue, and aggregation into fiber clumps, which is commonly known as silicosis. At the same time, it is accompanied by emphysema and bullae, making the ceramic industry a high-risk industry for silicosis. In addition, since the birth of ceramic rock slabs, the entire ceramic rock slab industry has had the phenomenon of cracking during late cold processing, with losses reaching 5%-8%. This is one of the main reasons why the production cost of ceramic rock slabs has remained high, and has become a major pain point in the industry, restricting the application of ceramic rock slabs in many fields and affecting their promotion and future development. The main reason for this phenomenon is that more crystalline silica is introduced into the raw materials and the crystalline silica undergoes a crystal transformation during the firing process, resulting in greater stress. Also, because the specifications of ceramic rock slabs are large, the absolute value of the residual stress after cooling is also large, making it very easy to crack during the production, cutting and processing processes.
[0004] Based on this, the present invention provides an environmentally friendly, easy-to-process ceramic rock slab with low crystalline silicon dioxide content and a production method thereof, which can significantly reduce the crystalline silicon dioxide content in the dust generated in the production process of the ceramic rock slab, and significantly reduce the crystalline silicon dioxide content in the physical phase composition of the green layer of the produced ceramic rock slab, thereby effectively reducing the risk of contracting silicosis during the production and processing of the ceramic rock slab, and at the same time reducing the stress generated in the ceramic rock slab due to the crystal transformation of silicon dioxide, thereby improving the machinability of the ceramic rock slab, and reducing the loss caused by cracking in the later cold processing of the ceramic rock slab. Summary of the invention
[0005] In order to solve the problems of high risk of silicosis caused by high crystalline silica content and high breakage rate during late cold processing in the existing ceramic rock slab production and processing, the present invention provides an environmentally friendly, easy-to-process ceramic rock slab with low crystalline silica content and a production method thereof.
[0006] The present invention uses an innovative design of a low-crystalline silicon dioxide content ceramic rock blank formulation system and a highly efficient linkage control of a firing system, so as to minimize the introduction of crystalline silicon dioxide SiO2 (C r ), on the other hand, a small amount of crystalline silicon dioxide SiO2 (C r ) is converted into amorphous silicon dioxide as much as possible during the sintering process of the slab body and silicon dioxide that exists as a component in other crystalline phases except crystalline silicon dioxide. Amorphous silicon dioxide belongs to the glass state and is wrapped on the surface of some crystalline phases (calcium feldspar, albite, mullite, cordierite, corundum, etc.). Together with other glass phases and gas phases, it constitutes the microstructure of the ceramic slab body, which is the crystalline silicon dioxide SiO2 (C p ) is reduced from the weight percentage to 10% or less, which can effectively reduce the risk of silicosis during the production, polishing, cutting and other processes of ceramic rock slabs. In addition, the stress generated by the crystal transformation of silicon dioxide during the firing process is reduced, and the residual stress of the finished ceramic rock slab is small, which makes the rock slab easy to process and reduces the loss caused by cracking during late cold processing.
[0007] In a first aspect, the present invention provides an environmentally friendly, easy-to-process ceramic rock slab with low crystalline silica content.
[0008] A low-crystalline silicon dioxide content environmentally friendly easy-to-process ceramic rock plate, comprising a body layer and a decorative layer arranged on the upper surface of the body layer, wherein the body layer has a phase composition of crystalline silicon dioxide SiO2 (C p ) The content by weight percentage is ≤10%.
[0009] The phase composition refers to the content of the crystalline phase, glass phase and gas phase in the ceramic rock slab blank layer by weight percentage. The crystalline phase is the dominant phase that determines the basic performance of the ceramic rock slab, including crystalline silica, calcium feldspar, albite, mullite, cordierite, corundum, etc. Its type, content, existence, etc. will affect the performance of the ceramic rock slab; the glass phase refers to the low-melting component in the ceramic rock slab blank layer, and its content, distribution, etc. will affect the performance of the ceramic rock slab; the gas phase (pores) is inevitable in the production process of ceramic rock slabs, and generally has a very small content in the ceramic rock slab blank layer. Its existence, content, and distribution state also affect the performance of the ceramic rock slab.
[0010] In the present application, crystalline silicon dioxide refers to silicon dioxide in the form of a crystalline phase in the physical composition of a ceramic slab raw material or a ceramic slab blank layer, wherein silicon dioxide in the form of a crystalline phase in the physical composition of a ceramic slab raw material is denoted as SiO2 (C r ); Silicon dioxide in the form of a crystalline phase in the phase composition of the ceramic rock slab green body layer is denoted as SiO2 (C p ).
[0011] As a further solution, the chemical composition of the green body layer by weight percentage includes: SiO2(T) 58%-65%, Al2O3 22%-28.5%, Fe2O3 0-3%, CaO 0.5%-7%, MgO 0.5%-5%, K2O 1.5%-5%, Na2O 0.35%-3%, and the remainder is impurities.
[0012] In the present application, SiO2(T) refers to the sum of silicon dioxide existing in the crystalline phase in the ceramic rock slab green body layer, silicon dioxide existing in the glass phase, and silicon dioxide existing as a component in other crystalline phases except crystalline silicon dioxide.
[0013] As a further solution, the content of the glass phase in the physical composition of the green body layer is 69.0%-88.5% by weight.
[0014] As a further solution, the chemical components of the glass phase in the physical phase composition of the green body layer include, by weight percentage: SiO2(A) 59.98%-67%, Al2O3 20.82%-27%, Fe2O3 0-2.64%, CaO 0.65%-5.85%, MgO0.57%-6.49%, K2O 1.95%-6.26%, Na2O 0.5%-3.76%, and TiO2 0-0.78%.
[0015] In the present application, SiO2(A) refers to the normalized content of amorphous silicon dioxide in the glass phase in the physical composition of the ceramic slab green body layer, expressed in weight percentage.
[0016] Specifically, the SiO2 (A) comes from the melting of crystalline silica and feldspar during the firing process of the ceramic rock slab body on the one hand, and comes from the decomposition product of clay minerals such as kaolin in the raw materials of the ceramic rock slab body during the firing process of the ceramic rock slab body on the other hand.
[0017] As a further solution, in the physical composition of the green body layer, the amount percentage of silicon dioxide SiO2 (E) in the glass phase exceeding the stoichiometric ratio of feldspar is ≥ 27.0%.
[0018] SiO2(E) refers to the percentage of silicon dioxide in the glass phase that exceeds the stoichiometric ratio of feldspar in the physical composition of the ceramic slab green body layer, including the part of crystalline silicon dioxide in the raw material dissolved into the glass phase and the part brought in by the decomposition of clay minerals.
[0019] As a further solution, in the physical composition of the green body layer, in the glass phase, n(CaO+MgO) / n(CaO+MgO+K2O+Na2O)≥0.350.
[0020] In the present application, n(CaO+MgO) refers to the sum of the percentages of CaO and MgO in the glass phase in the physical phase composition of the ceramic rock slab body layer after normalization and calculated by the amount of substance; n(CaO+MgO+K2O+Na2O) refers to the sum of the percentages of CaO, MgO, K2O and Na2O in the glass phase in the physical phase composition of the ceramic rock slab body layer after normalization and calculated by the amount of substance.
[0021] CaO and MgO are generally used as excellent fluxes in the building ceramics industry, and their main function is to reduce the maximum firing temperature of the brick blank and reduce the high-temperature viscosity and surface tension of the melt. The present application innovatively designs a low-crystalline silicon dioxide content ceramic rock slab blank formulation system to increase the proportion of alkaline earth metal oxides (CaO and MgO) in the glass network modifier (CaO, MgO, K2O and Na2O), so that the ceramic rock slab can avoid the phenomenon of raw firing due to excessively high temperature or over-firing due to excessively low temperature of the blank layer, and increase the flux content of the blank layer of the ceramic rock slab, thereby increasing the solubility of the glass relative to crystalline silicon dioxide in the physical phase composition of the blank layer during the firing process of the ceramic rock slab, so that a small amount of crystalline silicon dioxide SiO2 (C r ) is more converted into amorphous silicon dioxide and silicon dioxide existing as a component in other crystalline phases except crystalline silicon dioxide, which effectively reduces the crystalline silicon dioxide SiO2 (C p) content, while increasing the content of the glass phase in the physical composition of the green body layer, and subsequently also increasing the amount percentage of silicon dioxide in the glass phase in the physical composition of the green body layer that exceeds the stoichiometric ratio of feldspar.
[0022] As a further solution, the fracture toughness of the low crystalline silica content environmentally friendly easy-to-process ceramic rock plate is ≥1.2MPa·m 1 / 2 , modulus of rupture ≥50MPa.
[0023] As a further solution, the low-crystalline silica content, environmentally friendly, easy-to-process ceramic rock slab is processed in accordance with the machinability test method in the T / CBCSA 40-2021 "Ceramic Rock Slab" standard to achieve first-level machinability.
[0024] In a second aspect, the present invention provides a method for producing an environmentally friendly and easy-to-process ceramic rock plate with a low crystalline silicon dioxide content, which comprises the following steps: S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, wherein the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 55.68%-62%, Al2O3 20.5%-27.36%, Fe2O3 0-2.88%, CaO 0.48%-6.52%, MgO 0.47%-4.8%, K2O 1.44%-4.8%, Na2O 0.33%-2.8%, ignition loss 4%-7%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1150-1250°C, the firing cycle is 55-150min, and the holding time at the highest firing temperature is ≥7min; S6, post-processing of the semi-finished ceramic rock slab: post-processing the semi-finished ceramic rock slab to obtain a finished ceramic rock slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, wherein the phase composition of the body layer is crystalline silicon dioxide SiO2 (C p ) The content by weight percentage is ≤10%.
[0025] As a further scheme, in step S1, when preparing black ceramic rock slab slurry, the raw materials for preparing the ceramic rock slab slurry are: ball clay A, washed soil A, washed soil B, kaolin A, calcined soil A, potassium feldspar A, potassium feldspar B, potassium sodium feldspar A, potassium sodium feldspar B, wollastonite A, raw talc A, raw talc B, calcined bauxite B, and diopside; when preparing white ceramic rock slab slurry, the raw materials for preparing the ceramic rock slab slurry are: ball clay B, rock mud, kaolin B, calcined soil B, raw talc B, wollastonite A, wollastonite B, potassium feldspar A, potassium feldspar B, talc, TM2106 frit, fused quartz, calcined alumina A, calcined alumina B, bone ash, calcined bauxite A, and calcined bauxite B.
[0026] As a further solution, in step S1, the ball milling system is an intermittent ball milling system or a continuous ball milling system.
[0027] As a further solution, in step S2, before spray-drying the ceramic rock slab green body slurry obtained in step S1, the ceramic rock slab green body slurry is subjected to slurry preheating treatment.
[0028] Specifically, preheating the ceramic rock slab green body slurry refers to the process of transporting the ceramic rock slab green body slurry to a mud servo tank before the ceramic rock slab green body slurry is spray-dried, and heating the ceramic rock slab green body slurry to above 80°C through the hot air and mud gas / liquid type heat exchanger in the cold section at the tail of the kiln; preheating the ceramic rock slab green body slurry can increase the temperature and fluidity of the ceramic rock slab green body slurry, thereby reducing the energy consumption of the spray drying process in step S2, improving the energy utilization efficiency, increasing the production capacity, and achieving the purpose of energy saving and consumption reduction.
[0029] As a further solution, in step S6, the post-processing includes polishing, edge grinding, and applying nanofluid.
[0030] As a further solution, in step S1, the screening is performed using a 80-150 mesh vibrating screen, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a residue of 2.5%-3.5%, the specific gravity is 1.68-1.74 g / ml, and the flow rate is NK-2 Iwata viscosity cup 16-32s.
[0031] As a further solution, in step S2, the moisture content of the ceramic rock slab green body powder is 5.5%-7.5%, and the particle size is 45%-55% after 40 mesh sieve.
[0032] As a further solution, in step S3, the pressing pressure of the molding equipment is 35-42 MPa.
[0033] Residual stress is a key factor affecting the machinability of ceramic rock slabs. Only by reducing the residual stress to the lowest level possible can the risk of cracking of ceramic rock slabs during production and cutting be reduced, and the produced ceramic rock slabs have excellent machinability. Among them, the maximum firing temperature of the ceramic rock slab blank is 1150-1250℃, the firing cycle is 55-150min, and the holding time at the maximum firing temperature is ≥7min. Compared with traditional porcelain tiles, the holding time at the maximum firing temperature is extended, and the heating and cooling rates are slowed down. Delaying the heating rate during the firing process of the ceramic rock slab blank and extending the holding time at the maximum firing temperature are, on the one hand, beneficial to the small amount of crystalline silicon dioxide SiO2 (C r ) is converted into glass phase and silicon dioxide existing as a component in other crystalline phases except crystalline silicon dioxide, so that the crystalline silicon dioxide SiO2 (C r ) is further reduced; on the other hand, it is beneficial to the oxidation and decomposition of humus in the ceramic rock slab blank, thereby increasing the density of the blank layer and improving the fracture toughness of the ceramic rock slab. Delaying the heating and cooling rates can extend the interval of the crystal phase transformation of crystalline silicon dioxide in the blank layer and make the crystal phase transformation slow and uniform, reduce the volume effect of crystalline silicon dioxide caused by the crystal phase transformation of the ceramic rock slab during the firing process, and completely release the internal stress in the blank layer, thereby effectively reducing the residual stress in the blank layer. In addition, the ceramic rock slab blank itself has a low crystalline silicon dioxide content, and part of the crystalline silicon dioxide is converted into glass phase and silicon dioxide in other crystalline phases other than crystalline silicon dioxide during the firing process. The absolute value of the residual stress of the ceramic rock slab after cooling is also small, and it is not easy to break during production, cutting and processing, and has excellent machinability. Refer to the machinability test method in the T / CBCSA 40-2021 "Ceramic Rock Slab" standard for processing to achieve first-level machinability.
[0034] As a further solution, the chemical composition of the green body layer by weight percentage includes: SiO2(T) 58%-65%, Al2O3 22%-28.5%, Fe2O3 0-3%, CaO 0.5%-7%, MgO 0.5%-5%, K2O 1.5%-5%, Na2O 0.35%-3%, and the remainder is impurities.
[0035] As a further solution, in step S6, the content of the glass phase in the phase composition of the green body layer is 69.0%-88.5% by weight, and the chemical components of the glass phase in the phase composition of the green body layer include: SiO2(A) 59.98%-67%, Al2O3 20.82%-27%, Fe2O3 0-2.64%, CaO 0.65%-5.85%, MgO 0.57%-6.49%, K2O 1.95%-6.26%, Na2O 0.5%-3.76%, TiO2 0-0.78%, the amount percentage of silicon dioxide SiO2(E) in the glass phase in the physical phase composition of the green body layer that exceeds the stoichiometric amount of feldspar is ≥27.0%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is ≥0.350.
[0036] As a further solution, the fracture toughness of the low crystalline silica content environmentally friendly easy-to-process ceramic rock plate is ≥1.2MPa·m 1 / 2 , modulus of rupture ≥50MPa.
[0037] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses an innovative design of a low-crystalline silicon dioxide content ceramic rock slab blank formulation system and a highly efficient linkage control of a firing system to produce a low-crystalline silicon dioxide content environmentally friendly easy-to-process ceramic rock slab blank layer with a phase composition of crystalline silicon dioxide SiO2 (C p ) The content by weight percentage is ≤10%, which greatly reduces the content of crystalline silicon dioxide in the dust generated during the production process of ceramic rock panels, and greatly reduces the content of crystalline silicon dioxide in the phase composition of the green layer of the produced ceramic rock panels, effectively reducing the risk of silicosis during the production and processing of ceramic rock panels, and conforming to the national call for green, healthy and environmentally friendly production; (2) The present invention realizes efficient control through linkage of the firing system of low-crystalline silica content ceramic rock slabs, so that the small amount of crystalline silica originally introduced into the raw materials is further reduced during the firing process of the ceramic rock slab blank. At the same time, the volume effect of crystalline silica caused by the crystal transformation during the cooling process of the ceramic rock slab is reduced, and the residual stress in the blank layer is reduced. The low-crystalline silica content ceramic rock slab thus obtained has greater fracture toughness and fracture modulus. It is processed according to the machinability test method in the T / CBCSA 40-2021 "Ceramic Rock Slab" standard and achieves first-level machinability, which effectively reduces the high loss rate of the rock slab caused by cracking due to later cold processing.
[0038] (3) The present invention preheats the ceramic rock slab green body slurry by means of hot air and mud gas / liquid heat exchanger in the cold section at the rear of the kiln before the ceramic rock slab green body slurry is spray-dried, thereby reducing the energy consumption of the spray drying process, improving the energy utilization efficiency, increasing the production capacity, and achieving the purpose of energy saving and consumption reduction.
[0039] (4) Most of the raw materials used in the production of ceramic rock slabs with low crystalline silicon dioxide content in the present invention are raw materials used for conventional ceramic rock slab blanks. It is only necessary to make systematic adjustments to the process parameter configuration based on the existing ceramic rock slab production line without adding other equipment. The production process is economical and environmentally friendly, and the process is highly controllable. DETAILED DESCRIPTION
[0040] In order to make the technical solution and advantages of the present invention clearer, the technical solution of the present invention is described more clearly and completely in combination with specific embodiments. In the embodiments, the equipment used is the same as the production equipment used for conventional ceramic rock panels unless otherwise specified. Example 1
[0041] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 55.82%, Al2O3 26.15%, Fe2O3 1.62%, CaO 1.78%, MgO2.81%, K2O 3.72%, Na2O 2.48%, ignition loss 5.26%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1214°C, the firing cycle is 88.9 minutes, and the holding time at the highest firing temperature is 25.0 minutes; S6, post-processing of the semi-finished ceramic slab: The semi-finished ceramic slab is post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, denoted as T1. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) is 0% by weight.
[0042] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: ball clay A, washed clay A, raw talc B, calcined clay A, potassium-sodium feldspar A, and potassium feldspar A.
[0043] In step S1 , the ball milling system is a continuous ball milling system.
[0044] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0045] In step S1, a 100-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 3.14%, the specific gravity is 1.719 g / ml, and the flow rate is NK-2 Iwata viscosity cup 26s.
[0046] In step S2, the moisture content of the ceramic rock slab green body powder is 6.8%, and the particle size is 51.4% of the 40-mesh residue.
[0047] In step S3, the pressure of the molding equipment during compression molding is 37.5 MPa.
[0048] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 58.92%, Al2O3 27.60%, Fe2O31.71%, CaO 1.88%, MgO 2.97%, K2O 3.93%, Na2O 2.62%, and the balance is impurities.
[0049] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 88.50%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 63.03%, Al2O3 22.10%, Fe2O3 1.57%, CaO 2.12%, MgO 3.36%, K2O 4.44%, Na2O 2.96%, TiO2 0.42%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 27.1%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.562. Example 2
[0050] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 57.27%, Al2O3 25.93%, Fe2O3 1.63%, CaO 0.83%, MgO1.85%, K2O 3.68%, Na2O 2.48%, ignition loss 5.98%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1250°C, the firing cycle is 55.0 min, and the holding time at the highest firing temperature is 23.7 min; S6, post-processing of semi-finished ceramic slabs: post-processing the semi-finished ceramic slabs to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, denoted as T2. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 2.0% by weight.
[0051] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: ball clay A, washed clay A, raw talc B, calcined clay A, potassium-sodium feldspar A, and potassium feldspar A.
[0052] In step S1 , the ball milling system is an intermittent ball milling system.
[0053] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0054] In step S1, an 80-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 3.50%, the specific gravity is 1.740 g / ml, and the flow rate is 32s of the NK-2 Iwata viscosity cup.
[0055] In step S2, the moisture content of the ceramic rock slab green body powder is 7.5%, and the particle size is 55.0% of the 40-mesh residue.
[0056] In step S3, the pressure of the molding equipment during compression molding is 35.0 MPa.
[0057] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 60.92%, Al2O3 27.57%, Fe2O31.73%, CaO 0.88%, MgO 1.97%, K2O 3.91%, Na2O 2.64%, and the balance is impurities.
[0058] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 88.00%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 63.87%, Al2O3 23.42%, Fe2O3 1.60%, CaO 1.00%, MgO 2.24%, K2O 4.44%, Na2O 3.00%, TiO2 0.43%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer that exceeds the stoichiometric amount of feldspar is 30.8%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.436. Example 3
[0059] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 60.52%, Al2O3 20.50%, Fe2O3 0%, CaO 6.52%, MgO 0.47%, K2O 1.95%, Na2O 2.80%, ignition loss 6.82%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1179°C, the firing cycle is 122.9 minutes, and the holding time at the highest firing temperature is 22.4 minutes; S6, post-processing of semi-finished ceramic slabs: The semi-finished ceramic slabs are post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T3. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 3.0% by weight.
[0060] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, ball clay B, TM2106 frit, kaolin B, and calcined clay B.
[0061] In step S1 , the ball milling system is a continuous ball milling system.
[0062] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0063] In step S1, a 120-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 2.79%, the specific gravity is 1.697 g / ml, and the flow rate is NK-2 Iwata viscosity cup 21s.
[0064] In step S2, the moisture content of the ceramic rock slab green body powder is 6.1%, and the particle size is 47.9% of the 40-mesh residue.
[0065] In step S3, the pressure of the molding equipment during compression molding is 40.0 MPa.
[0066] The chemical composition of the green body layer, measured by weight percentage, includes: SiO2(T) 64.95%, Al2O3 22.00%, Fe2O30%, CaO 7.00%, MgO 0.50%, K2O 2.09%, Na2O 3.00%, and the balance is impurities.
[0067] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 87.00%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 66.33%, Al2O3 20.87%, Fe2O3 0%, CaO 5.85%, MgO 0.57%, K2O 2.40%, Na2O 3.45%, TiO2 0.53%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 27.0%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.594. Example 4
[0068] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 56.17%, Al2O3 26.91%, Fe2O3 2.70%, CaO 2.68%, MgO0.82%, K2O 3.40%, Na2O 2.18%, ignition loss 4.90%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1243°C, the firing cycle is 61.8 minutes, and the holding time at the highest firing temperature is 21.1 minutes; S6, post-processing of semi-finished ceramic slabs: The semi-finished ceramic slabs are post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T4. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 4.0% by weight.
[0069] In step S1, the raw materials for preparing ceramic rock slab green body slurry are: washed soil A, raw talc A, calcined bauxite B, potassium feldspar A, potassium feldspar A, and kaolin A.
[0070] In step S1 , the ball milling system is an intermittent ball milling system.
[0071] In step S2, before spray drying the ceramic rock slab green body slurry obtained in step S1, the ceramic rock slab green body slurry is subjected to slurry preheating treatment.
[0072] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0073] In step S1, an 80-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 3.43%, the specific gravity is 1.736 g / ml, and the flow rate is 31s of NK-2 Iwata viscosity cup.
[0074] In step S2, the moisture content of the ceramic rock slab green body powder is 7.4%, and the particle size is 54.3% of the 40-mesh residue.
[0075] In step S3, the pressure of the molding equipment during compression molding is 35.5 MPa.
[0076] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 59.06%, Al2O3 28.30%, Fe2O32.84%, CaO 2.82%, MgO 0.86%, K2O 3.57%, Na2O 2.29%, and the balance is impurities.
[0077] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 86.23%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 60.00%, Al2O3 27.00%, Fe2O3 2.50%, CaO 2.41%, MgO 1.00%, K2O 4.14%, Na2O 2.66%, TiO2 0.30%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 27.3%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.439. Example 5
[0078] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 58.89%, Al2O3 25.11%, Fe2O3 1.89%, CaO 1.72%, MgO0.97%, K2O 4.27%, Na2O 2.24%, ignition loss 4.72%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab, wherein the highest firing temperature of the high temperature firing is 1236°C, the firing cycle is 68.6 minutes, and the holding time at the highest firing temperature is 19.9 minutes; S6, post-processing of the semi-finished ceramic slab: The semi-finished ceramic slab is post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T5. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 4.5% by weight.
[0079] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: ball clay A, washed soil A, washed soil B, wollastonite A, potassium-sodium feldspar B, raw talc A, potassium feldspar B, calcined bauxite B, and diopside.
[0080] In step S1 , the ball milling system is a continuous ball milling system.
[0081] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0082] In step S1, an 80-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 3.36%, the specific gravity is 1.731 g / ml, and the flow rate is 30s of NK-2 Iwata viscosity cup.
[0083] In step S2, the moisture content of the ceramic rock slab green body powder is 7.2%, and the particle size is 53.6% of the 40-mesh residue.
[0084] In step S3, the pressure of the molding equipment during compression molding is 36.0 MPa.
[0085] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 61.81%, Al2O3 26.36%, Fe2O31.98%, CaO 1.80%, MgO 1.02%, K2O 4.48%, Na2O 2.35%, and the balance is impurities.
[0086] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 85.57%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 63.25%, Al2O3 24.05%, Fe2O3 1.94%, CaO 1.36%, MgO 1.19%, K2O 5.24%, Na2O 2.75%, TiO2 0.23%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer that exceeds the stoichiometric amount of feldspar is 27.8%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.350. Example 6
[0087] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder used for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 60.49%, Al2O3 21.77%, Fe2O3 0.26%, CaO 4.85%, MgO2.49%, K2O 3.01%, Na2O 1.10%, ignition loss 5.87%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1186°C, the firing cycle is 116.1min, and the holding time at the highest firing temperature is 18.6min; S6, post-processing of semi-finished ceramic slabs: The semi-finished ceramic slabs are post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T6. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 6.5% by weight.
[0088] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: wollastonite A, raw talc B, potassium feldspar B, ball clay B, pyrophyllite, kaolin B, and calcined clay B.
[0089] In step S1 , the ball milling system is an intermittent ball milling system.
[0090] In step S2, before spray drying the ceramic rock slab green body slurry obtained in step S1, the ceramic rock slab green body slurry is subjected to slurry preheating treatment.
[0091] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0092] In step S1, a 120-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 2.86%, the specific gravity is 1.701 g / ml, and the flow rate is NK-2 Iwata viscosity cup 22s.
[0093] In step S2, the moisture content of the ceramic rock slab green body powder is 6.2%, and the particle size is 48.6% after 40 mesh sieve.
[0094] In step S3, the pressure of the molding equipment during compression molding is 39.5 MPa.
[0095] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 64.19%, Al2O3 23.59%, Fe2O30.30%, CaO 4.88%, MgO 2.68%, K2O 3.14%, Na2O 1.02%, and the balance is impurities.
[0096] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 79.41%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 65.53%, Al2O3 21.67%, Fe2O3 0.38%, CaO 3.73%, MgO 3.19%, K2O 3.95%, Na2O 1.28%, TiO2 0.26%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 38.3%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.700. Example 7
[0097] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 59.91%, Al2O3 23.12%, Fe2O3 0%, CaO 4.69%, MgO 1.96%, K2O 4.51%, Na2O 1.16%, ignition loss 4.65%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1150°C, the firing cycle is 150.0 min, and the holding time at the highest firing temperature is 17.3 min; S6, post-processing of the semi-finished ceramic slab: The semi-finished ceramic slab is post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T7. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 6.7% by weight.
[0098] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: rock mud, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, and potassium feldspar A.
[0099] In step S1 , the ball milling system is a continuous ball milling system.
[0100] In step S2, before spray drying the ceramic rock slab green body slurry obtained in step S1, the ceramic rock slab green body slurry is subjected to slurry preheating treatment.
[0101] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0102] In step S1, a 150-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 2.50%, the specific gravity is 1.680 g / ml, and the flow rate is 16s of the NK-2 Iwata viscosity cup.
[0103] In step S2, the moisture content of the ceramic rock slab green body powder is 5.5%, and the particle size is 45.0% after 40 mesh sieve.
[0104] In step S3, the pressure of the molding equipment during compression molding is 42.0 MPa.
[0105] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 62.83%, Al2O3 24.25%, Fe2O30%, CaO 4.92%, MgO 2.06%, K2O 4.73%, Na2O 1.21%, and the balance is impurities.
[0106] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 78.80%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 65.18%, Al2O3 21.00%, Fe2O3 0%, CaO 4.08%, MgO 2.21%, K2O 6.00%, Na2O 1.54%, TiO2 0%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 27.1%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.591. Example 8
[0107] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 58.74%, Al2O3 23.70%, Fe2O3 0.26%, CaO 4.77%, MgO2.45%, K2O 3.44%, Na2O 1.34%, ignition loss 5.13%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab, wherein the highest firing temperature of the high temperature firing is 1171°C, the firing cycle is 129.6min, and the holding time at the highest firing temperature is 16.0min; S6, post-processing of semi-finished ceramic slabs: The semi-finished ceramic slabs are post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T8. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 7.0% by weight.
[0108] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: rock mud, wollastonite A, raw talc B, potassium feldspar B, pyrophyllite, kaolin B, calcined clay B, potassium feldspar A, and calcined bauxite B.
[0109] In step S1 , the ball milling system is an intermittent ball milling system.
[0110] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0111] In step S1, a 150-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 2.71%, the specific gravity is 1.693 g / ml, and the flow rate is 19s of NK-2 Iwata viscosity cup.
[0112] In step S2, the moisture content of the ceramic rock slab green body powder is 5.9%, and the particle size is 47.1% of the 40-mesh residue.
[0113] In step S3, the pressure of the molding equipment during compression molding is 40.5 MPa.
[0114] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 62.05%, Al2O3 25.01%, Fe2O30.25%, CaO 5.08%, MgO 2.62%, K2O 3.46%, Na2O 1.32%, and the balance is impurities.
[0115] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 78.11%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 63.00%, Al2O3 23.52%, Fe2O3 0.32%, CaO 3.92%, MgO 2.84%, K2O 4.43%, Na2O 1.69%, TiO2 0.28%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer that exceeds the stoichiometric amount of feldspar is 30.9%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.655. Example 9
[0116] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 60.56%, Al2O3 22.69%, Fe2O3 0.27%, CaO 4.23%, MgO2.34%, K2O 4.80%, Na2O 0.85%, ignition loss 4.01%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab, wherein the highest firing temperature of the high temperature firing is 1164°C, the firing cycle is 136.4 minutes, and the holding time at the highest firing temperature is 14.7 minutes; S6, post-processing of the semi-finished ceramic slab: The semi-finished ceramic slab is post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T9. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 7.2% by weight.
[0117] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina A, and kaolin B.
[0118] In step S1 , the ball milling system is a continuous ball milling system.
[0119] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0120] In step S1, a 150-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 2.64%, the specific gravity is 1.689 g / ml, and the flow rate is 18s of the NK-2 Iwata viscosity cup.
[0121] In step S2, the moisture content of the ceramic rock slab green body powder is 5.8%, and the particle size is 46.4% after 40 mesh sieve.
[0122] In step S3, the pressure of the molding equipment during compression molding is 41.0 MPa.
[0123] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 63.09%, Al2O3 23.64%, Fe2O30.28%, CaO 4.41%, MgO 2.44%, K2O 5.00%, Na2O 0.89%, and the balance is impurities.
[0124] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 77.91%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 64.10%, Al2O3 20.82%, Fe2O3 0.35%, CaO 4.16%, MgO 2.88%, K2O 6.26%, Na2O 1.11%, TiO2 0.31%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 27.3%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.634. Example 10
[0125] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 57.66%, Al2O3 23.26%, Fe2O3 0.23%, CaO 4.58%, MgO2.53%, K2O 3.06%, Na2O 1.18%, ignition loss 6.48%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1193°C, the firing cycle is 109.3min, and the holding time at the highest firing temperature is 13.4min; S6, post-processing of the semi-finished ceramic slab: The semi-finished ceramic slab is post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T10. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 7.3% by weight.
[0126] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, wollastonite B, potassium feldspar B, ball clay B, pyrophyllite, kaolin B, bone ash, and calcined bauxite A.
[0127] In step S1 , the ball milling system is an intermittent ball milling system.
[0128] In step S2, before spray drying the ceramic rock slab green body slurry obtained in step S1, the ceramic rock slab green body slurry is subjected to slurry preheating treatment.
[0129] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0130] In step S1, a 120-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 2.93%, the specific gravity is 1.706 g / ml, and the flow rate is 23s of NK-2 Iwata viscosity cup.
[0131] In step S2, the moisture content of the ceramic rock slab green body powder is 6.4%, and the particle size is 49.3% of the 40-mesh residue.
[0132] In step S3, the pressure of the molding equipment during compression molding is 39.0 MPa.
[0133] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 62.16%, Al2O3 24.95%, Fe2O30.40%, CaO 4.73%, MgO 2.97%, K2O 3.29%, Na2O 1.17%, and the balance is impurities.
[0134] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 77.51%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 63.09%, Al2O3 23.12%, Fe2O3 0.51%, CaO 3.45%, MgO 3.65%, K2O 4.25%, Na2O 1.51%, TiO2 0.41%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 33.9%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.687. Embodiment 11
[0135] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder used for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 60.28%, Al2O3 21.69%, Fe2O3 0.19%, CaO 4.89%, MgO1.65%, K2O 3.79%, Na2O 1.07%, ignition loss 5.59%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab, wherein the highest firing temperature of the high temperature firing is 1207°C, the firing cycle is 95.7 minutes, and the holding time at the highest firing temperature is 12.1 minutes; S6, post-processing of the semi-finished ceramic slab: The semi-finished ceramic slab is post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T11. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 7.5% by weight.
[0136] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, kaolin B, and bone ash.
[0137] In step S1 , the ball milling system is a continuous ball milling system.
[0138] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0139] In step S1, a 100-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 3.07%, the specific gravity is 1.714 g / ml, and the flow rate is 25s of NK-2 Iwata viscosity cup.
[0140] In step S2, the moisture content of the ceramic rock slab green body powder is 6.6%, and the particle size is 50.7% of the 40-mesh residue.
[0141] In step S3, the pressure of the molding equipment during compression molding is 38.0 MPa.
[0142] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 63.91%, Al2O3 23.50%, Fe2O30.32%, CaO 4.78%, MgO 1.97%, K2O 4.03%, Na2O 1.37%, and the balance is impurities.
[0143] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 77.31%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 65.40%, Al2O3 21.77%, Fe2O3 0.41%, CaO 3.08%, MgO 2.19%, K2O 5.22%, Na2O 1.77%, TiO2 0.16%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer that exceeds the stoichiometric amount of feldspar is 31.7%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.566. Example 12
[0144] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 55.68%, Al2O3 27.36%, Fe2O3 2.88%, CaO 0.48%, MgO4.80%, K2O 1.44%, Na2O 2.78%, ignition loss 4.00%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1229°C, the firing cycle is 75.4 minutes, and the holding time at the highest firing temperature is 10.9 minutes; S6, post-processing of semi-finished ceramic slabs: post-processing the semi-finished ceramic slabs to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, denoted as T12. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 7.8% by weight.
[0145] In step S1, the raw materials for preparing ceramic rock slab green body slurry are: ball clay A, washed soil A, washed soil B, wollastonite A, potassium feldspar B, raw talc A, potassium feldspar B, and calcined bauxite B.
[0146] In step S1 , the ball milling system is an intermittent ball milling system.
[0147] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0148] In step S1, an 80-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 3.29%, the specific gravity is 1.727 g / ml, and the flow rate is NK-2 Iwata viscosity cup 29s.
[0149] In step S2, the moisture content of the ceramic rock slab green body powder is 7.1%, and the particle size is 52.9% of the 40-mesh residue.
[0150] In step S3, the pressure of the molding equipment during compression molding is 36.5 MPa.
[0151] The chemical composition of the green body layer, measured by weight percentage, includes: SiO2(T) 58.00%, Al2O3 28.50%, Fe2O33.00%, CaO 0.50%, MgO 5.00%, K2O 1.50%, Na2O 2.90%, and the remainder is impurities.
[0152] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 77.07%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 59.98%, Al2O3 23.75%, Fe2O3 2.64%, CaO 0.65%, MgO 6.49%, K2O 1.95%, Na2O 3.76%, TiO2 0.78%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 32.2%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.681. Embodiment 13
[0153] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 62.00%, Al2O3 22.38%, Fe2O3 0.05%, CaO 4.04%, MgO1.81%, K2O 3.85%, Na2O 1.12%, ignition loss 4.62%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab, wherein the highest firing temperature of the high temperature firing is 1221°C, the firing cycle is 82.1min, and the holding time at the highest firing temperature is 9.6min; S6, post-processing of semi-finished ceramic slabs: The semi-finished ceramic slabs are post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T13. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 8.0% by weight.
[0154] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, kaolin B, and fused quartz.
[0155] In step S1 , the ball milling system is a continuous ball milling system.
[0156] In step S2, before spray drying the ceramic rock slab green body slurry obtained in step S1, the ceramic rock slab green body slurry is subjected to slurry preheating treatment.
[0157] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0158] In step S1, a 100-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 3.21%, the specific gravity is 1.723 g / ml, and the flow rate is NK-2 Iwata viscosity cup 27s.
[0159] In step S2, the moisture content of the ceramic rock slab green body powder is 6.9%, and the particle size is 52.1% of the 40-mesh residue.
[0160] In step S3, the pressure of the molding equipment during compression molding is 37.0 MPa.
[0161] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 65.00%, Al2O3 23.46%, Fe2O30.05%, CaO 4.24%, MgO 1.90%, K2O 4.04%, Na2O 1.17%, and the balance is impurities.
[0162] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 76.91%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 67.00%, Al2O3 21.51%, Fe2O3 0.06%, CaO 2.53%, MgO 1.95%, K2O 5.26%, Na2O 1.52%, TiO2 0.18%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 36.2%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.539. Embodiment 14
[0163] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 57.98%, Al2O3 22.63%, Fe2O3 0.12%, CaO 6.10%, MgO3.82%, K2O 1.63%, Na2O 0.33%, ignition loss 7.00%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab. The highest firing temperature of the high temperature firing is 1157°C, the firing cycle is 143.2 minutes, and the holding time at the highest firing temperature is 8.3 minutes; S6, post-processing of semi-finished ceramic slabs: The semi-finished ceramic slabs are post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T14. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 8.5% by weight.
[0164] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, ball clay B, TM2106 frit, kaolin B, and calcined clay B.
[0165] In step S1 , the ball milling system is an intermittent ball milling system.
[0166] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0167] In step S1, a 150-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 2.57%, the specific gravity is 1.684 g / ml, and the flow rate is 17s of the NK-2 Iwata viscosity cup.
[0168] In step S2, the moisture content of the ceramic rock slab green body powder is 5.6%, and the particle size is 45.7% of the 40-mesh residue.
[0169] In step S3, the pressure of the molding equipment during compression molding is 41.5 MPa.
[0170] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 62.34%, Al2O3 24.33%, Fe2O30.13%, CaO 6.56%, MgO 4.11%, K2O 1.75%, Na2O 0.35%, and the balance is impurities.
[0171] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 70.00%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 63.88%, Al2O3 21.84%, Fe2O3 0.19%, CaO 5.50%, MgO 5.00%, K2O 2.50%, Na2O 0.50%, TiO2 0.60%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 42.7%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.866. Embodiment 15
[0172] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 60.11%, Al2O3 22.30%, Fe2O3 0.19%, CaO 5.45%, MgO4.09%, K2O 1.46%, Na2O 0.40%, ignition loss 5.82%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1200°C, the firing cycle is 102.5min, and the holding time at the highest firing temperature is 7.0min; S6, post-processing of the semi-finished ceramic slab: The semi-finished ceramic slab is post-processed to obtain a finished ceramic slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, which is recorded as T15. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) has a content of 10.0% by weight.
[0173] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, kaolin B, and bone ash.
[0174] In step S1 , the ball milling system is a continuous ball milling system.
[0175] In step S6, post-processing includes polishing, edge grinding, and applying nanofluid.
[0176] In step S1, a 120-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 3.00%, the specific gravity is 1.710 g / ml, and the flow rate is 24s of the NK-2 Iwata viscosity cup.
[0177] In step S2, the moisture content of the ceramic rock slab green body powder is 6.5%, and the particle size is 50.0% of the 40-mesh residue.
[0178] In step S3, the pressure of the molding equipment during compression molding is 38.5 MPa.
[0179] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 63.83%, Al2O3 23.68%, Fe2O30.20%, CaO 5.79%, MgO 4.34%, K2O 1.55%, Na2O 0.42%, and the balance is impurities.
[0180] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 69.00%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 64.93%, Al2O3 21.74%, Fe2O3 0.29%, CaO 4.57%, MgO 5.33%, K2O 2.25%, Na2O 0.61%, TiO2 0.28%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer that exceeds the stoichiometric amount of feldspar is 46.3%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.864. Comparative Example Comparative Example 1
[0181] The same as Example 15, except that the raw material ratio for preparing the ceramic rock slab green body slurry is different, denoted as D1. In step S2, the chemical composition of the ceramic rock slab green body powder calculated by dry weight percentage includes: SiO2 63.97%, Al2O3 23.55%, Fe2O3 0.39%, CaO 0.47%, MgO 0.11%, K2O 1.39%, Na2O 5.53%, loss on ignition 4.30%, and the remainder is impurities.
[0182] In step S6, the phase composition of the green body layer is crystalline silicon dioxide SiO2 (C p ) has a content of 10.1% by weight.
[0183] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 66.84%, Al2O3 24.61%, Fe2O30.41%, CaO 0.49%, MgO 0.11%, K2O 1.45%, Na2O 5.78%, and the balance is impurities.
[0184] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 68.53%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 69.00%, Al2O3 20.09%, Fe2O3 0.60%, CaO 0.57%, MgO 0.16%, K2O 2.12%, Na2O 7.01%, TiO2 0.45%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 21.0%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.095. Comparative Example 2
[0185] The same as Example 5, except that the raw material ratio for preparing the ceramic rock slab green body slurry is different, denoted as D2. In step S2, the chemical composition of the ceramic rock slab green body powder measured by dry weight percentage includes: SiO2 65.73%, Al2O3 19.55%, Fe2O3 0.33%, CaO 1.52%, MgO 0.48%, K2O 2.88%, Na2O 2.78%, loss on ignition 6.46%, and the remainder is impurities.
[0186] In step S6, the phase composition of the green body layer is crystalline silicon dioxide SiO2 (C p ) has a content of 21.7% by weight.
[0187] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 70.27%, Al2O3 20.91%, Fe2O30.35%, CaO 1.63%, MgO 0.51%, K2O 3.08%, Na2O 2.97%, and the balance is impurities.
[0188] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 65.60%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 67.76%, Al2O3 19.13%, Fe2O3 0.53%, CaO 2.35%, MgO 0.78%, K2O 4.69%, Na2O 4.32%, TiO2 0.43%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 21.8%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.340. Comparative Example 3
[0189] The same as Example 3, except that the raw material ratio for preparing the ceramic rock slab green body slurry is different, denoted as D3. In step S2, the chemical composition of the ceramic rock slab green body powder measured by dry weight percentage includes: SiO2 67.82%, Al2O3 20.59%, Fe2O3 0.20%, CaO 0.33%, MgO 0.22%, K2O 4.82%, Na2O 0.87%, loss on ignition 4.79%, and the remainder is impurities.
[0190] In step S6, the phase composition of the green body layer is crystalline silicon dioxide SiO2 (C p ) has a content of 28.6% by weight.
[0191] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 71.23%, Al2O3 21.62%, Fe2O30.21%, CaO 0.34%, MgO 0.23%, K2O 5.06%, Na2O 0.91%, and the balance is impurities.
[0192] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 58.70%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 66.47%, Al2O3 21.38%, Fe2O3 0.35%, CaO 0.58%, MgO 0.40%, K2O 8.62%, Na2O 1.53%, TiO2 0.67%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is 26.5%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.149. Comparative Example 4
[0193] Same as Example 15, except that the holding time at the highest firing temperature is 6.0 min, denoted as D4. In step S6, the phase composition of the green body layer is crystalline silicon dioxide SiO2 (C p ) has a content of 12.0% by weight.
[0194] In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 67.02%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2 (A) 63.90%, Al2O3 22.34%, Fe2O3 0.30%, CaO 4.77%, MgO 5.47%, K2O 2.31%, Na2O 0.63%, TiO2 0.28%, the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer that exceeds the stoichiometric amount of feldspar is 44.4%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is 0.865. Performance Test Example Performance Test Example 1
[0195] The ceramic rock slabs prepared in Examples 1-15 (T1-T15) and Comparative Examples 1-4 (D1-D4) were respectively subjected to the following performance tests according to the following standards, and the results are shown in Table 1 below.
[0196] Table 1 Ceramic rock plate performance test results T1 T2 T3 T4 T5 T6 T7 T8 T9 T10 T11 T12 T13 T14 T15 D1 D2 D3 D4 <![CDATA[SiO2(C p )(wt %)]]> 0.0 2.0 3.0 4.0 4.5 6.5 6.7 7.0 7.2 7.3 7.5 7.8 8.0 8.5 10.0 10.1 21.7 28.6 12.0 <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> 2.00 1.94 1.89 1.83 1.77 1.71 1.66 1.60 1.54 1.49 1.43 1.37 1.31 1.26 1.20 1.18 0.94 0.79 1.12 Modulus of rupture (MPa) 100.0 96.4 92.9 89.3 85.7 82.1 78.6 75.0 71.4 67.9 64.3 60.7 57.1 53.6 50.0 48.2 39.5 37.2 45.7 Machinability Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 2 Level 3 Level 3 Level 2 Fracture toughness: The indentation method is used for testing. The specific process is as follows: The surface of the test sample is first polished to a mirror surface. On a microhardness tester, a 10kg load is applied to the polished surface with a conical diamond indenter of the hardness tester to produce an indentation. This creates prefabricated cracks at the four vertices of the indentation. The fracture toughness value (K IC ). The calculation formula is:
[0197] Among them, Young's modulus E is in GPa, load P is in N, crack length C is in mm, microhardness H is V The unit is GPa.
[0198] Modulus of rupture: The modulus of rupture is determined according to GB / T 3810.4-2016 "Test methods for ceramic tiles Part 4: Determination of modulus of rupture and breaking strength".
[0199] Machinability: Processing shall be carried out in accordance with the machinability test method in the T / CBCSA 40-2021 "Ceramic Rock Slab" standard.
[0200] In this application, the phase composition of the green body layer of the ceramic rock plate is crystalline silicon dioxide SiO2 (C p ) It is most intuitive to determine whether the ceramic rock plate is environmentally friendly by measuring the content by weight percentage. From the above table, it can be seen that the crystalline silicon dioxide SiO2 (C p ) by weight percentage is 10% or less. Whether in the early stage of ceramic slab raw material processing or in the later stage of ceramic slab product cutting, grinding and other processing, it will not produce a lot of high crystalline silicon dioxide content respirable dust, which effectively reduces the risk of silicosis in the production and processing of ceramic slabs. In addition, due to the crystalline silicon dioxide SiO2 (C p ) content by weight percentage is low, the stress generated by the crystal transformation of silicon dioxide in the ceramic rock plate is small, the machinability of the ceramic rock plate reaches the first level, and the loss caused by the cracking of the ceramic rock plate during the later cold processing is also small. The ceramic rock plates D1-D4 produced in comparative examples 1-4 are produced according to the process conditions of Example 15, Example 5, Example 3, and Example 15, respectively. However, since the raw materials for preparing the ceramic rock plate blank slurry of D1, D2, D3 and T15, T5, and T3 are the same but in different proportions, and the holding time at the highest firing temperature of D4 and T15 is different, the crystalline silicon dioxide SiO2 (C p) are all higher than 10% by weight, and the risk of silicosis is high during the production and processing of ceramic rock panels. Secondly, due to the phase composition of the green layer of ceramic rock panels D1-D4, the crystalline silicon dioxide SiO2 (C p ) has a high content in terms of weight percentage, and the stress generated by the crystal transformation of silicon dioxide in the ceramic rock slab is relatively large. The machinability of the ceramic rock slab has not reached the first level, and the loss caused by the cracking of the ceramic rock slab during the later cold processing is also large. The above data objectively reflect that the ceramic rock slab produced by this application has been significantly improved in terms of environmental protection and processing performance. In particular, the ceramic rock slab product produced in Example 1 will not produce high-crystalline silicon dioxide content respirable dust during the cutting, grinding and other processing processes, and the risk of suffering from silicosis is very low. It also has good toughness, high strength and good machinability.
[0201] Fracture toughness and fracture modulus are the most important data that determine the high toughness, high strength and machinability of ceramic rock plates. From the above table, it can be seen that the fracture toughness of ceramic rock plates T1-T15 produced in Examples 1-15 is all within 1.20 MPa·m 1 / 2 and above, the modulus of rupture is 50 MPa and above, and the machinability is first-class. The D1 produced in Comparative Example 1 according to the process conditions of Example 15 is different from T15 in that the raw material ratio for preparing the ceramic rock slab green body slurry is different, and the content of the glass phase in the phase composition of the green body layer is 68.53% by weight, which is lower than 69.00%. The glass phase is relatively small, and there is not enough glass phase to stick to the crystalline phase. The bonding force between the crystalline phases is low, resulting in the fracture toughness of D1 being less than 1.20 MPa·m 1 / 2 , the modulus of rupture is less than 50MPa, and secondly, the corresponding crystalline silicon dioxide SiO2 (C p ) is higher than 10% by weight, and the crystalline silicon dioxide undergoes a crystal transformation during the firing process to generate greater stress, resulting in the machinability reaching only level 2; Comparative Examples 2 and 3 are produced according to the process conditions of Example 5 and Example 3, respectively. D2 and D3 are different from T5 and T3 in that the raw materials for preparing the ceramic rock slab green body slurry are the same but the proportions are different. In the phase composition of the green body layer of D2, n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase is 0.340, which is lower than 0.350, the amount percentage of silica SiO2 (E) in the glass phase in the phase composition of the green body layer of D3 that exceeds the stoichiometric amount of feldspar is 26.5%, which is lower than 27.0%, and the corresponding n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the phase composition of the green body layer of D3 is 0.149, which is lower than 0.350, resulting in insufficient solubility of the glass phase in the phase composition of the green body layer during the firing process of the ceramic rock plate to the crystalline silica, causing a small amount of crystalline silica SiO2 (Cr ) is not good at converting into amorphous silicon dioxide and silicon dioxide existing as a component in other crystalline phases except crystalline silicon dioxide, so the crystalline silicon dioxide SiO2 (C p ) is higher in weight percentage, and the corresponding machinability level is lower, only level 3; Comparative Example 4 D4 produced according to the process conditions of Example 15 is different from T15 in that the holding time at the highest firing temperature is 6 min, which is lower than 7 min. Due to the insufficient holding time at the highest firing temperature, on the one hand, a small amount of crystalline silicon dioxide SiO2 (C r ) does not have enough time to transform into the glass phase and the silica that exists as a component in other crystalline phases except crystalline silica. On the other hand, it is not conducive to the oxidative decomposition of humus in the ceramic rock slab blank, which leads to a decrease in the density of the blank layer. Therefore, the fracture toughness and rupture modulus of D4 are lower than those of T15, and the machinability only reaches level 2. This fully demonstrates the feasibility of the scheme for improving the machinability of ceramic rock slabs in this application and the obvious advantages of machinability.
[0202] According to the disclosure and guidance of the above description, those skilled in the art to which the present application belongs may also change and modify the above implementation. Therefore, the present application is not limited to the specific implementation disclosed and described above, and the modification and change of the application should also fall within the protection scope of the claims of the present application. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present application.
Claims
1. An environmentally friendly and easy-to-process ceramic rock plate with low crystalline silicon dioxide content, characterized by: It comprises a body layer and a decorative layer arranged on the upper surface of the body layer, wherein the body layer has a phase composition of crystalline silicon dioxide SiO2 (C p ) The content by weight percentage is ≤10%.
2. The low crystalline silicon dioxide content environmentally friendly easy-to-process ceramic rock plate according to claim 1 is characterized by: The chemical composition of the green body layer by weight percentage includes: SiO2(T) 58%-65%, Al2O3 22%-28.5%, Fe2O3 0-3%, CaO 0.5%-7%, MgO 0.5%-5%, K2O 1.5%-5%, Na2O 0.35%-3%, and the remainder is impurities.
3. The low crystalline silicon dioxide content environmentally friendly easy-to-process ceramic rock plate according to claim 1 is characterized by: The content of the glass phase in the phase composition of the green body layer is 69.0%-88.5% by weight.
4. The low crystalline silicon dioxide content environmentally friendly easy-to-process ceramic rock plate according to claim 3 is characterized by: The chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include SiO2(A) 59.98%-67%, Al2O3 20.82%-27%, Fe2O3 0-2.64%, CaO 0.65%-5.85%, MgO 0.57%-6.49%, K2O 1.95%-6.26%, Na2O 0.5%-3.76%, and TiO2 0-0.78%.
5. The low crystalline silicon dioxide content environmentally friendly easy-to-process ceramic rock plate according to claim 4 is characterized by: In the physical phase composition of the green body layer, the amount percentage of silicon dioxide SiO2 (E) in the glass phase exceeding the stoichiometric ratio of feldspar is ≥ 27.0%.
6. The low crystalline silicon dioxide content environmentally friendly easy-to-process ceramic rock plate according to claim 4 is characterized by: In the physical composition of the green body layer, in the glass phase, n(CaO+MgO) / n(CaO+MgO+K2O+Na2O)≥0.
350.
7. The low crystalline silicon dioxide content environmentally friendly easy-to-process ceramic rock plate according to claim 1 is characterized by: The fracture toughness of the environmentally friendly and easy-to-process ceramic rock plate with low crystalline silicon dioxide content is ≥1.2MPa·m 1 / 2 , modulus of rupture ≥50MPa.
8. The low crystalline silicon dioxide content environmentally friendly easy-to-process ceramic rock plate according to claim 1 is characterized by: The low-crystalline silicon dioxide content, environmentally friendly, easy-to-process ceramic rock slab is processed according to the machinability test method in the T / CBCSA 40-2021 "Ceramic Rock Slab" standard to achieve first-level machinability.
9. A method for producing environmentally friendly and easy-to-process ceramic rock slabs with low crystalline silicon dioxide content, characterized in that: The following steps are involved: S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, wherein the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 55.68%-62%, Al2O3 20.5%-27.36%, Fe2O3 0-2.88%, CaO0.48%-6.52%, MgO 0.47%-4.8%, K2O 1.44%-4.8%, Na2O 0.33%-2.8%, ignition loss 4%-7%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1150-1250°C, the firing cycle is 55-150min, and the holding time at the highest firing temperature is ≥7min; S6, post-processing of the semi-finished ceramic rock slab: post-processing the semi-finished ceramic rock slab to obtain a finished ceramic rock slab comprising a body layer and a decorative layer arranged on the upper surface of the body layer, wherein the phase composition of the body layer is crystalline silicon dioxide SiO2 (C p ) content by weight percentage ≤ 10%.
10. The method for producing environmentally friendly and easy-to-process ceramic rock slabs with low crystalline silicon dioxide content according to claim 9, characterized in that: In step S1, when preparing black ceramic rock slab slurry, the raw materials for preparing the ceramic rock slab slurry are: ball clay A, washed soil A, washed soil B, kaolin A, calcined soil A, potassium feldspar A, potassium feldspar B, potassium sodium feldspar A, potassium sodium feldspar B, wollastonite A, raw talc A, raw talc B, calcined bauxite B, and diopside; when preparing white ceramic rock slab slurry, the raw materials for preparing the ceramic rock slab slurry are: ball clay B, rock mud, kaolin B, calcined soil B, raw talc B, wollastonite A, wollastonite B, potassium feldspar A, potassium feldspar B, pyrophyllite, TM2106 frit, fused quartz, calcined alumina A, calcined alumina B, bone ash, calcined bauxite A, and calcined bauxite B.
11. The method for producing environmentally friendly and easy-to-process ceramic rock slabs with low crystalline silicon dioxide content according to claim 9, characterized in that: In step S1, the ball milling system is an intermittent ball milling system or a continuous ball milling system; In step S2, before spray drying the ceramic rock slab green body slurry obtained in step S1, the ceramic rock slab green body slurry is subjected to slurry preheating treatment; In step S6, the post-processing includes polishing, edge grinding, and applying nanofluid.
12. The method for producing environmentally friendly and easy-to-process ceramic rock slabs with low crystalline silicon dioxide content according to claim 9, characterized in that: In step S1, the sieving is performed using a 80-150 mesh vibrating screen, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 2.5%-3.5%, the specific gravity is 1.68-1.74 g / ml, and the flow rate is NK-2 Iwata viscosity cup 16-32s; In step S2, the moisture content of the ceramic rock slab green body powder is 5.5%-7.5%, and the particle size is 45%-55% of the 40-mesh residue; In step S3, the pressure of the molding equipment during compression molding is 35-42 MPa; In step S6, the content of the glass phase in the physical phase composition of the green body layer by weight percentage is 69.0%-88.5%, the chemical components of the glass phase in the physical phase composition of the green body layer by weight percentage include: SiO2(A) 59.98%-67%, Al2O3 20.82%-27%, Fe2O3 0-2.64%, CaO 0.65%-5.85%, MgO 0.57%-6.49%, K2O 1.95%-6.26%, Na2O 0.5%-3.76%, TiO2 0-0.78%, the amount percentage of silicon dioxide SiO2(E) in the glass phase in the physical phase composition of the green body layer exceeding the stoichiometric amount of feldspar is ≥27.0%, and n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is ≥0.350.
Citation Information
Patent Citations
Low-temperature fast-fired ceramic rock plate and preparation method thereof
CN115010465A
High-toughness and high-strength building ceramic rock slab and preparation method thereof
CN115838274A
Glass ceramic material, method of forming glass ceramic material and use of glass ceramic material
CN116157368A
Low-expansion ceramic blank, low-expansion ceramic rock plate as well as preparation method and application of low-expansion ceramic blank
CN116813305A
Large ceramic sheet and manufacturing method therefor
JP2018168055A